Prince Lander & the Dragon War - Smith, S. D. (Sam Smith) (Smith, S. D. (Sam Smith) Tales of Old Natalia, 2022)
"Old Natalia, during the declining years of Whitson Mariner and the rise of tyrannical dragons and their master, Namoz Dragonking. Rabbitkind faces extinction, and Prince Lander must follow his aging father to the last desperate edge of hope. A possible future is glimpsed dimly through a veil of darkness and death. This will not be a safe ending. Blood calls. Oathbreakers attack. Allies fracture. Legends end."--